The mastery of physics concepts between students are learning by ICT and laboratory experiments based-teaching - Nggadas, Drikben Eka Putra; Ariswan, Ariswan (Universitas PGRI Kanjuruhan Malang, 2019)
The study aimed to examine differences in the mastery of physics concepts between students are learning by ICT based-teaching and laboratory experiments based-teaching. The particular research was quasi-experiment with a pretest-posttest design with nonequivalent groups. The sample size was three classes selected from the population of students on class X of SMA N 4 Kupang. The data collection method used multiple choice questions tests. Data analysis used independent samples t-test using SPSS 16.0 for Windows. The results of data analysis using t-test at a significance level of 0.05 indicated that there was a difference in the average mastery of physics concepts between students are learning by ICT based-teaching and the laboratory experiments based-teaching. The mean score of the mastery of physics concept on students are learning by ICT based-teaching was higher than students are learning by laboratory experiments based-teaching.